Prevalência de esclerose lateral amiotrófica no estado do Rio Grande do Sul - Linden Junior, Eduardo (2012)
Amyotrophic lateral sclerosis is the most common disease of motor neurons in adults. Characterized by degeneration and death of motor neurons in the cortex, brainstem and spinal cord, being invariably fatal. Epidemiological studies have reported a relatively uniform frequency of amyotrophic lateral sclerosis in several parts of the world. However, most studies are conducted in Europe and North America. The purpose of this study was to determine the prevalence of amyotrophic lateral sclerosis in the State of Rio Grande do Sul, as well as to verify the relationship between the prevalence found in the city of Porto Alegre, capital of the State of Rio Grande do Sul, with the prevalence in the inland of the State of Rio Grande do Sul. Clinical characteristics of 81 patients with amyotrophic lateral sclerosis were described.Therefore, we conducted an active search for diagnostic cases of amyotrophic lateral sclerosis in specialized hospitals and clinics in Rio Grande do Sul, by contacting neurologists and neurophysiologists, and through the regional association of patients with amyotrophic lateral sclerosis. The prevalence of amyotrophic lateral sclerosis in Rio Grande do Sul on July 31, 2010 was 2.2 cases per 100,000 people (95% CI 2.0-2.5), with 5.0 cases per 100,000 people (95% CI 3.9-6.2) in Porto Alegre and 1.8 cases per 100,000 people (95% CI 1.6-2.1) in the inland of the state. The prevalence was higher for men, peaking in the age group 70-79 years in both genders. In the clinical description of some patients with amyotrophic lateral sclerosis, the median ages at onset of symptoms and diagnosis were, respectively, 54.2 ± 12.3 (ranging between 28.1 and 80.5) and 55.5 ± 12.4 (ranging between 29.0 and 80.9). The average time from onset of symptoms and diagnosis was 1.6 ± 1.4 years, and the initial symptom most frequently reported by patients was muscle weakness. Our findings are consistent with studies carried out in other parts of the world, especially those conducted in the city of Porto Alegre. In the description of cases, the average age at onset and at diagnosis was lower than that reported in other studies in the world, but similar to that described in other Brazilian studies.